2004
DOI: 10.1080/00365540310018833
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decrease of hepatitis B in a cohort of drug users followed over a period of 15 years: The impact of anti-HBV vaccination

Abstract: In the Western world, the population at the highest risk of HBV infection is probably that of illicit drug users (DUs). Since 1985, 1 Public Health Centre for Drug Users (PHCDU), in north-eastern Italy, has been asking all heroin DUs, whether in treatment or not, to undergo screening for HIV, HBV and, since 1989, for HCV infection. Since 1988 the Centre has proposed HBV vaccination to all patients who were negative for all HBV markers. From 1985 to 2001 895 heroin DUs were screened, 726 males and 169 females. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…These programs commenced in Victoria, Australia's second most populous state, in 1998 and 2001, respectively, and their impact on PWID vaccination coverage and incident HBV infection has not been examined. In the USA and Europe, evidence of the impact of universal and/or targeted HBV vaccination policies is mixed …”
Section: Introductionmentioning
confidence: 99%
“…These programs commenced in Victoria, Australia's second most populous state, in 1998 and 2001, respectively, and their impact on PWID vaccination coverage and incident HBV infection has not been examined. In the USA and Europe, evidence of the impact of universal and/or targeted HBV vaccination policies is mixed …”
Section: Introductionmentioning
confidence: 99%
“…Based on Williams et al [16], we assumed vaccine effectiveness (VE) of 90%, 70% and 40% for three, two and one vaccine dose, respectively. Furthermore, we assumed that protection would last life-long [16,17]. The difference between the two scenarios serves as our estimate of then the number of avoided hepatitis B infections.…”
Section: Estimating the Number Of Avoided Hepatitis B Infectionsmentioning
confidence: 99%
“…Lugoboni et al (2004) showed that in Italy 88% of 320 DUs had received three or more vaccinations; however, in that cohort study, participants were studied over 15 years, and were followed up every 4 months. The extensive screening and the longer period that free vaccination was available in that study may explain the higher compliance among Italian DUs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies among DUs have reported completion rates of hepatitis B vaccination, varying from low completion rates (20%-31%;Des Jarlais et al, 2001;Christensen et al, 2004;Seal et al, 2003), to intermediate (41%-63%; Christensen et al, 2004;Lum et al, 2003;Ompad et al, 2004;McGregor, Marks, Hayward, Bell, and Slack, 2003;Van Houdt et al, 2006;Van Steenbergen, 2002), to high-compliance rates (66%-88%; Altice, Bruce, Walton, and Buitrago, 2005;Budd, Robertson, and Elton, 2004;Christensen et al, 2004;Des Jarlais et al, 2001;Lugoboni et al, 2004;Rogers and Lubman, 2005;Seal et al, 2003;Quaglio et al, 2002) depending on the use of different vaccination schedules, onsite vaccination possibilities, and the use of monetary incentives. However, only some of these studies identified social-demographic factors (age, ethnic background, and homelessness), and risk factors concerning drug use (i.e., injecting drug use) associated with vaccine completion (Altice et al, 2005;Lum et al, 2003;Ompad et al, 2004, Seal et al, 2003.…”
mentioning
confidence: 96%